Neuronal deficiency of HIF prolyl 4-hydroxylase 2 in mice improves ischemic stroke recovery in an HIF dependent manner - Li, Lexiao; Saliba, Pamela; Reischl, Stefan; Marti, Hugo; Kunze, Reiner (Neurobiology of disease, 2016)
Hypoxia inducible factors (HIFs) mediate the endogenous adaptive responses to hypoxia. HIF prolyl 4-hydroxylase domain proteins (PHD) are important suppressors of the HIF pathway. Recently, we demonstrated that neuron-specific deletion of Phd2 reduces cerebral tissue damage in the very acute phase of ischemic stroke. In the present study, we investigated whether neuronal Phd2 ablation is likewise beneficial for stroke recovery, and aimed to identify underlying cellular mechanisms. Mice underwent permanent occlusion of the distal middle cerebral artery (pdMCAO) for either 7days (sub-acute stage) or 30days (chronic stage). One week after pdMCAO the infarct size of Phd2-deficient mice was significantly reduced as compared to wild-type (WT) mice. Accordingly, Phd2-deficient animals showed less impaired sensorimotor function. Neuronal loss of Phd2 upregulated vascular endothelial growth factor (VEGF) and significantly increased microvascular density along the infarct border in the sub-acute stage of stroke. Phd2-deficient mice showed reduced expression of pro-inflammatory cytokines and increased numbers of resting microglia/macrophages and reactive astrocytes within peri-infarct regions in comparison to WT littermates. Finally, brain tissue protection and increased angiogenesis upon sub-acute ischemic stroke was completely absent in Phd2 knockout mice that were additionally deficient for both Hif1a and Hif2a. Our findings suggest that lack of PHD2 in neurons improves histological and functional long-term outcome from ischemic stroke at least partly by amplifying endogenous adaptive neovascularization through activation of the HIF-VEGF axis.